Acculturation of Islamic Values in Siraman Javanese and Bugis Wedding Traditions: A Comparative Study - Mohammad Nasih Al Hashas; Muh. Hafidh Ubaidillah; Achmad Alfaridzih (AN NUR: Jurnal Studi Islam, 2025)
This study comparatively examines the siraman tradition in Javanese traditional weddings and mappasau botting and cemme passih ceremonies in Bugis traditional weddings. This research is qualitative research with a content analysis approach, where the source data is obtained from literature studies. Through literature study, it was found that the two traditions have similarities in the main purpose of cleansing and purifying the bride-to-be outwardly and mentally before entering a new life. Both are full of spiritual meaning and the hope of blessings. The process of acculturation of local cultural values with Islamic teachings is seen in the use of symbols in both traditions. The difference lies in the procession, time of implementation, equipment, and interpretation of the meaning of symbols according to their respective cultural contexts. The religious aspect in both traditions is associated with the concept of bathing for purity, repulsion, and asking for forgiveness of sins according to Islamic teachings. This study concluded that although different processions, the traditional Javanese and Bugis flushing traditions is an effort to cleanse the inner birth in the hope of happiness in marriage within the framework of culture and Islam.